Analyzing the Risk Factors of Early Neonatal Deaths in Kupang District, Rural Eastern Indonesia - Sangguana Marthen Jacobus Koamesah; Idawati Trisno; Listyawati Nurina; Nicholas Edwin Handoyo; Mariana Archoon Sailana (Jurnal Syntax Admiration, 2024)
The neonatal mortality rate in East Nusa Tenggara (NTT) remains high, with 80% of neonatal deaths occurring in the early period. This study aims to analyze the risk factors contributing to early neonatal death in Kupang District. A retrospective case-control study was conducted, involving 31 cases of early neonatal death and 69 controls from medical records from January 2023 to June 2024. Multinomial logistic regression analysis was used to identify the influence of maternal health, birth, neonatal factors, and healthcare facility readiness. The results showed that birth weight, frequency of antenatal visits, and the completeness of medical equipment were significant predictors of early neonatal death. More frequent antenatal visits were found to reduce the risk of death by 24%, while low birth weight increased the risk by 30%. In conclusion, interventions focusing on preventing low birth weight, ensuring compliance with minimum antenatal visits, and improving the readiness of basic healthcare facilities could reduce early neonatal death in this region.